A commercial test of four hydraulic cements - Hanson, Gustaf William (My University, 1900)
Introduction: It was the intention of the writer to make a test of cements made only in Kansas; but being able to secure but two Kansas Cements, two other leading commercial brands were secured with which to make comparison. The cements that were put under test are as follows: Germania, a Portland cement, Iola, a Portland cement, Louisville, a natural cement, Fort Scott, a natural cement. The Germania is a Portland cement, made in Germany near the border of Belgium. It is classed as one of the leading Portland cements. Its color is a light grayish blue and it is a fine grain cement, working easily under the trowel. The Iola is a Portland cement, made by a plant just lately erected at Iola, Kansas, where natural gas is used as a fuel in calcining. The sample tested was made from the rock at Iola, which was shipped to the Company's plant in Michigan, and made there in order to find out what quality cement could be made from the material at Iola. The plant not being in operation when this test was begun, a sample of this cement was secured. The color of this cement is a little darker gray than the Germania and seems to be coarser as it works harder under the trowel and scratches more. The Louisville is a natural cement made mostly on the Indiana side of the Ohio River, near Louisville, Kentucky. The Fort Scott is a natural cement, made at Fort Scott, Kansas. It is very much like the Louisville. Both have a reddish brown color before mixing; but after setting the Louisville turns to a whiter color than the Fort Scott.
Citation: Hanson, Gustaf William. A commercial test of four hydraulic cements. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Hydraulic cements; Portland cements; Natural cements; Germania cements; Iola cements; Louisville cements; Fort Scott cements; Theses